Numerical Modelling for Design of Ram-compacted Bearing Base Piling Foundations - Du, Zhaodong (Curtin University, 2020)
This thesis presents a novel design method for RBB piles based on validated numerical modelling in ABAQUS. Two developed equations provided integrate five typical RBB piling parameters, involving a wide range of hypothetical cases of various RBB piling configurations, covering all actual soil types. The equations were calibrated with four historic cases; these have confirmed that the new predictions were economic and accurate, and the underestimation caused by the currently used design equations was eliminated.